A STYLISTIC ANALYSIS OF LANGUAGE USE IN KATHERINE MANSFIELD’S THE DOLL’S HOUSE - Julia Sukma; Otong Setiawan Djuharie (Jurnal Media Akademik (JMA), 2026)
The current study examines language use in the short story “The Doll’s House” by Katherine Mansfield from a stylistic analysis point of view and concentrates on the use of linguistic features with the purpose of creating narrative meaning and interpretational characteristics. The study aims to analyze specific words, phrases, clauses, and sentences that have certain stylistic preferences within the narrative. The research methodology applied in this study is that of qualitative description. This study has revealed that Mansfield was employing a very complicated vocabulary in order to create imagery effects and describe social stratification very delicately, and variations in the sentence structure, for instance short, exclamatory, and repetitive ones, covey the emotional attitudes of the child characters. Moreover, the present study finds that figurative language, especially the technique of personification, plays a symbolic role in the depiction of values like empathy and conscience. The study concludes that language in “The Doll’s House” is used not only in an aesthetic manner but is also employed to convey social meanings in the form of narration. Therefore, stylistic analysis “Methodology” is a valuable instrument for analyzing the connections between linguistic form and meaning in literary narrative texts like short stories.